2012
DOI: 10.1007/s10620-012-2305-2
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Spirochetosis: An Enigmatic Disease

Abstract: To date, our study is the largest case series that includes both endoscopic and pathologic descriptions and confirms the "bland" nature of the condition. In <20 % of our patients inflammation was present microscopically and it did not correlate well with endoscopic appearance. Symptoms reported by our patients were similar to those reported in previous studies, although our lack of endoscopic changes was different from one previous paper. There is no established standard of care for the treatment of IS and our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Members of the genus Borrelia , namely Borrelia burgdorferi s and Borrelia recurrentis , are important human pathogens that cause Lyme disease and relapsing fever, respectively (Dworkin et al, 2008; Nau et al, 2009; Cutler, 2010). Leptospira and Brachyspira , are members of the families Leptospiraceae and Brachyspiraceae , and causative agents of the diseases leptospirosis and intestinal spirochaetosis, respectively (Adler and de la Peña Moctezuma, 2010; Anthony et al, 2013; Euzéby, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Members of the genus Borrelia , namely Borrelia burgdorferi s and Borrelia recurrentis , are important human pathogens that cause Lyme disease and relapsing fever, respectively (Dworkin et al, 2008; Nau et al, 2009; Cutler, 2010). Leptospira and Brachyspira , are members of the families Leptospiraceae and Brachyspiraceae , and causative agents of the diseases leptospirosis and intestinal spirochaetosis, respectively (Adler and de la Peña Moctezuma, 2010; Anthony et al, 2013; Euzéby, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, while spirochetes are well-known causative pathogens of watery diarrhea in veterinary medicine [2], there are conflicting reports [3,4] as to whether human intestinal spirochetosis (HIS), which is mostly caused by Brachyspira aalborgi (B. aalborgi) or B. pilosicoli, is associated with symptoms of chronic diarrhea or irritable bowel syndrome. It is also reported that HIS may be responsible for colonic adenomas or hyperplastic polyps (HPs) [5], while its association with neoplasms remains largely unclear [3].…”
Section: Introductionmentioning
confidence: 99%
“…2 3 The significance of this finding and its role in human disease has been debated in the literature and generally colonic spirochaetosis (CS) is considered to be a commensal organism of no clinical or pathological significance 2 4…”
mentioning
confidence: 99%